2013
DOI: 10.11604/pamj.2013.16.30.1877
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing adherence to paediatric antiretroviral therapy in Portharcourt, South- South Nigeria

Abstract: IntroductionThe efficiency of antiretroviral therapy (ART) depends on a near-perfect level of patient's adherence. Adherence in children poses peculiar challenges. The aim of the study was to determine the adherence level and factors influencing adherence among HIV-infected children and adolescents in University of Port Harcourt Teaching Hospital, Nigeria.MethodsA cross-sectional survey of HIV-infected children and adolescents on ART using self-report by the caregiver/child in the past one month.ResultsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
35
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 22 publications
11
35
1
Order By: Relevance
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 85%
“…The use of treatment reminders was associated with better adherence while the use of PI-based regimens predicted poorer adherence. The adherence rate in the current study is better than those reported from several low, middle and high income countries (Bhattacharya & Dubey, 2011;Kim, Gerver, Fidler, & Ward, 2014;Nyogea et al, 2015;Reda & Biadgilign, 2012;Ugwu & Eneh, 2013). …”
Section: Discussioncontrasting
confidence: 85%
“…In this study, patient who had suboptimal adherence to their treatment had 4.85 times more risk of developing treatment failure which mirrors with other studies conducted in Nigeria, Tanzania, and Ethiopia (Ramadhani et al. 2007; Ugwu and Eneh 2013; Yimer and Yalew 2015). Another study in the public facility revealed that the risk factors for treatment failure include nonadherence and missed appointments (Gregory et al.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence in adolescents has been reported to be poorer than in younger children, and older adults in both resourced rich and limited settings [18]. Reasons include adolescents' risk taking behavior, the stage of development when thought and reasoning is not fully developed, and regimen fatigue [18,38]. As perinatally infected HIV children who have been on ARVs grow into adolescence, adherence was found to decrease because of long period on medication [18,19,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Reasons include adolescents' risk taking behavior, the stage of development when thought and reasoning is not fully developed, and regimen fatigue [18,38]. As perinatally infected HIV children who have been on ARVs grow into adolescence, adherence was found to decrease because of long period on medication [18,19,[36][37][38]. Some studies have reported adherence rates for long term prescription medications to be between 50-75% [18,19].…”
Section: Discussionmentioning
confidence: 99%